Zagraniczne bezzwrotne źródła finansowania rewitalizacji w Polsce - Kańduła, Sławomira (Foreign Non-Returnable Sources of Financing Revitalization in Poland, 2007)
Joining the European Union by Poland has created the possibility to gain external sources to finance projects connected with city's revitalization. The aim of the article is to point at potential existing sources of funds used for financing revitalization in Poland. The author describes also new sources: URBAN, JEREMIE, JESSICA.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 467-477